Family involvement for the achievement of school learning. A systematic review - Requena Cango , Marcela (Scripta Mundi, 2024)
This article addresses the systematic review of scientific publications about parental involvement in schoolwork for student learning achievements. This study aims to answer two basic questions: How does parental participation favor their sons and daughters learning achievements? How does the family involve in schoolwork? Which strategies should the school promote for the parental involvement? For this, the analysis of scientific publications was carried out in the period from 2021 to 2023, publications selected based on the methodology of the PRISMA 2020 declaration, assuming specific inclusion and exclusion criteria. The reviewed productions provide empirical and theoretical data in the field of family intervention in the process of parents support in order to reinforce schoolwork from home and the types of involvement in children’s school. The results show that this topic is of interest to researchers concerned with demonstrating that parental involvement becomes a key aspect for the achievement of learning and that the school must be the promoter of the bond that must be created in the family-school binomial..